The Role Of Trust In The Voluntary Compliance Of MSME Taxpayers - Risqi Aji Ardhianto; Icuk Rangga Bawono; Yudha Aryo Sudibyo (Universitas Muhammadiyah Malang, 2022)
This study aims to determine the effect of tax justice and the quality of tax service services on the voluntary compliance of MSME taxpayers in Pekalongan City with trust in the tax authority as an intervening variable. This research is a survey research with a quantitative approach. The data used in this study are primary data obtained from distributing questionnaires to 100 MSMEs registered in the Pekalongan Tax Office. The sample was selected by the purposive sampling technique. The collected data is processed and analyzed using the SmartPLS 3.0 application. The results of this study indicate that (1) tax justice has no effect on the voluntary compliance of MSME taxpayers, (2) the quality of tax service services has a positive effect on the voluntary compliance of MSME taxpayers, (3) trust in tax authorities has a positive effect on the voluntary compliance of MSME taxpayers, (4) trust in tax authorities can mediate the effect of tax justice on the voluntary compliance of MSME taxpayers, (5) trust in tax authorities can mediate the effect of tax service quality on the voluntary compliance of MSME taxpayers.